CYTOMEGALOVIRUS INFECTION OF THE UPPER GASTROINTESTINAL TRACT FOLLOWING LIVER TRANSPLANTATION—INCIDENCE, LOCATION, AND SEVERITY IN CYCLOSPORINE- AND FK506-TREATED PATIENTS, - Sakr, Mahmoud (1992)
One hundred and forty randomly selected liver transplant recipients were studied before and after primary orthotopic liver transplantation for the presence or absence of CMV enteritis. Following OLTx, 65 patients were treated with cyclosporine A and 75 were treated with FK506. The two groups were similar with regard to the incidence, location, and outcome of their upper gastrointestinal CMV infection. Prior to OLTx, only one patient had evidence of enteric CMV infection. The incidence of CMV enteritis post-OLTx was 27.7% in the CsA-treated group and 20% in the FK-treated group. During the first posttransplant month, no patient in the FK-treated group developed CMV enteritis, compared with 11.5% of the patients who were treated with CsA (P<0.05). Gastric CMV was found in over 80% of those positive for any organ in either group. In addition to CMV infection of the upper gastrointestinal tract, clinically evident CMV disease involved more nonenteric organs in the CsA-treated group than in the FK-treated group. In the CsA-treated group, CMV-negative patients had a statistically higher 1-year survival rate (100%) than CMV-positive patients (77.8%) (P<0.05). In the FK-treated group, no difference in survival was observed between CMV-positive or CMV-negative cases at 1 year. Of the patients on CsA, 20% received OKT3 for persistent rejection, as compared with 13% in the FK-treated group. The patients receiving both CsA and OKT3 had a higher rate of upper gastrointestinal CMV infection than did FK-treated patients who also received OKT3 therapy (38.5% versus 20%, respectively). Based upon these data, it can be concluded that (1) patients receiving FK have a lower incidence of enteric CMV infection; (2) following OLTx, upper gastrointestinal CMV infection presents later in FK-treated patients; (3) the stomach is the most frequently involved organ in the UGIT; (4) FK-treated liver recipients have less severe enteric CMV infection than do CsA-treated patients; (5) enteric CMV is not a major cause of mortality in liver transplant recipients; and (6) in patients receiving FK, those who require OKT3 therapy do not appear to be at a greater risk for the development of CMV enteritis than those who do not.